2022
DOI: 10.1021/acs.jpclett.2c00825
|View full text |Cite
|
Sign up to set email alerts
|

Water Diffusion Proceeds via a Hydrogen-Bond Jump Exchange Mechanism

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 52 publications
2
33
0
Order By: Relevance
“…The only way to reconcile these contradictory decays is that the rotation of the OH arm is such that it re-establish the OO contact. This is the jump rotation motion advertised in recent investigations [48,49,50], and is found to be contained in the dynamics of a classical model of water. For alcohols, it is the opposite which is found, namely that the OO decay is faster than the OH decay, denoting that the hydrogen bonding holds the hydroxyl group clusters.…”
Section: Analysis Of Dynamical Correlation Functionssupporting
confidence: 57%
See 1 more Smart Citation
“…The only way to reconcile these contradictory decays is that the rotation of the OH arm is such that it re-establish the OO contact. This is the jump rotation motion advertised in recent investigations [48,49,50], and is found to be contained in the dynamics of a classical model of water. For alcohols, it is the opposite which is found, namely that the OO decay is faster than the OH decay, denoting that the hydrogen bonding holds the hydroxyl group clusters.…”
Section: Analysis Of Dynamical Correlation Functionssupporting
confidence: 57%
“…However, it is the dynamical correlations which reveal the dierence between the similarities in dierent micro-states (snapshots) and the strong dierences on how the system evolves in time from one microstate to another. Our analysis shows that it is this dynamical evolution which explains several features observed previously in the literature, such as the jump rotation of the OH arm for water [48,49,50], or the contradictory pictures of the importance of the wa-ter structure [51,33,52,14,37,39,38,40,41]. Perhaps the water tetrahedrality has been put too much at the center of water local structure [33,12,35,36],…”
Section: Discussionmentioning
confidence: 48%
“…In liquid water, the dynamics span time scales from subpicosecond in-place H-bond fluctuations to picosecond H-bond lifetimes and nano/microsecond diffusion rates. 58 Indeed, water dynamics are considered "fractal" in character; each time scale, no matter how short or how long, can be associated with a corresponding ensemble motion. This is particularly important in biomolecular systems, where the time scales of biomolecules can similarly span multiple orders of magnitude in time.…”
Section: Crowding Effects On H-bond Dynamicsmentioning
confidence: 99%
“…Indeed, recent studies have demonstrated that proton dynamics in liquid water can be well captured if the training set contains sufficient data points corresponding to proton transfers. 16…”
Section: Machine-learned Approximations To the Energies Of Atomistic ...mentioning
confidence: 99%
“…Indeed, recent studies have demonstrated that proton dynamics in liquid water can be well captured if the training set contains sufficient data points corresponding to proton transfers. 16 In practice, the currently most popular software for parametrizing and utilizing MLPs in electrocatalysis are LASP 17 and DeepMD. 18,19 The power of the former is the availability of a large set of predefined MLPs, while the latter has very powerful active-learning capabilities, enabling an efficient parametrization of system-specific MLPs.…”
Section: Zhi Wei Sehmentioning
confidence: 99%